EFFECT OF LIVELIHOOD DIVERSIFICATION AND TECHNOLOGY ADOPTION ON FOOD SECURITY STATUS OF RICE FARMING HOUSEHOLDS IN OGUN STATE. NIGERIA - Osagie John Afodu; Afolami Carolyn Afolake; Balogun Olubunmi Lawrence (Agricultural Socio-Economics Journal, 2020)
This study assesses the effect of livelihood diversification and technology adoption on food security status among rice farming households in the Ogun State Nigeria. Farming households in Africa have increasingly sought means of escaping from the detrimental consequences of poverty by inclining to diversification of their activities; within and outside the farm sector. A multistage sampling technique was used to select 158 rice farmers. A well-structured questionnaire was used to collect data for the study. The data were analyzed using descriptive statistics, Simpson Index, adoption index and logit regression model. Factors affecting food security of the rice farmers were Simpson Index of Diversification (γ1= 0.320, p= 5%), Technologies Adoption Index (γ2=1.019, p=5%), household size (γ5= -0.060, p= 10%), educational status of the farmers (γ6= 0.035 , p= 5%), farm size (γ7= 0.133, p= 5%) and access to credit (γ9= 0.405, p= 10%). It was recommended that rice farmers should be educated on modern technologies in rice production. Credit facilities should be made available for the rice farming household either by the government or private organizations to enhance farming activities, alleviate poverty and increase household food security.